Pengaruh Jenis Pelarut dan Ukuran Partikel Bahan terhadap Karakteristik Ekstrak Daun Bidara (Ziziphus mauritiana L.) sebagai Sumber Saponin - Lumbanraja, Ika Martoquito; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p06, 2019)
Bidara (Ziziphus mauritiana L.) is widely grown in the tropics. Bidara is rich in benefits because it has content of saponins contained in the leaves. Saponins compounds derived plants can be used as soap foaming agents. Saponins can be applied in the manufacture of soap because of its nature as a natural surfactant. The purpose of this study were to determine the influence of solvent type and particle size of materials againts on the characteristics bidara leaf extract as a source of saponins, get the best solvent type and particle size to produce bidara leaf extract as a source of saponins. This study used a Randomized Block Design with treatment of solvent type and particle size of materials. Treatment of solvent type consists of 3 levels, namely: methanol, ethanol and acetone. The particle size of materials treatment also consists of 3 levels, namely: 40 mesh, 60 mesh and 80 mesh. Each treatment are grouped into two-based implementation. The results showed that treatment of solvent type and particle size of materials very significant effect on yield, coarse extract saponins content and foam height leaves bidara as a source of saponins. Interaction between treatments very significant effect on yield and foam height. However, significant effect on coarse extract saponins content bidara leaves. The methanol solvent type treatment with particle size of material 80 mesh is the best treatment to produce bidara leaf extract as a source of saponins with value yield of 17.91±0.73 %, 20.40 ± 0.79% coarse extract saponins content and foam height of 8.27 ± 0.01 mm. Keywords : Ziziphus mauritina L., saponins, extraction, solvent type, the particle size of material.